2008
DOI: 10.3950/jibiinkoka.111.594
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Methotrexate-associated Lymphoproliferative Disorder (MTX-LPD)

Abstract: Methotrexate (MTX) has been increasingly administered to patients with rheumatoid arthritis (RA), resulting in methotrexate-associated lymphoproliferative disorder (MTX-LPD) in patients. We reported three case of rheumatoid arthritis (RA) undergoing methotrexate (MTX) therapy who developed MTX-LPD. A 72-year-old woman treated with MTX since December 1997 (total dose 3684 mg) presented with swelling of the right tonsil in October 2006, and diffuse large B-cell lymphoma was diagnosed by tonsil biopsy and positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This patient with latency type III tumor also had similar regression results. On the contrary, Ishida et al interestingly reported EBV-positive MTX-LPD diagnosed in a swollen tonsil biopsy [ 16 ]. It spontaneously regressed after withdrawal of MTX, and the follow-up specimens from the tonsil became EBV-negative and free of LPD.…”
Section: Discussionmentioning
confidence: 99%
“…This patient with latency type III tumor also had similar regression results. On the contrary, Ishida et al interestingly reported EBV-positive MTX-LPD diagnosed in a swollen tonsil biopsy [ 16 ]. It spontaneously regressed after withdrawal of MTX, and the follow-up specimens from the tonsil became EBV-negative and free of LPD.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other lymphomas, lymphomas due to MTX-LPD tend to manifest more frequently as extranodal lesions and are common in the gastrointestinal tract, skin, lungs, and soft tissues. In the head and neck regions, such lymphomas are seen in the cervical lymph nodes and tonsils; as extranodal lesions, they have been seen in the salivary glands, thyroid glands, and tooth buds [3,6,[9][10][11][12]. The histopathological presentations of MTX-LPD are diverse, with the most common diffuse large B-cell lymphoma accounting for 35%-60% of cases, followed by Hodgikin lymphoma and follicular lymphoma, which account for 12%-25% and 5%-10%, respectively [3-6, 10, 13].…”
Section: Discussionmentioning
confidence: 99%
“…The skin, lungs, gastrointestinal tract, spleen, oral cavity, and kidneys may be involved as the extranodal LPD sites [3]. In the head and neck regions, the palatine tonsil, epipharynx, gingiva, tongue, salivary gland, thyroid gland, and nasal cavity have also been reported as the extranodal LPD sites [4,5,8].…”
Section: Introductionmentioning
confidence: 99%